A new vision of the role of the formation of competitive specialists in engineering and economics after the Great Patriotic War in the development of the economy and society - Antonov S. A. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
this work reveals the historical facts of the development of the Moscow Institute of Engineering and Economics in order to demonstrate the role of unique Soviet educational organizations in the development of the post-war economy and society. A brief description of engineering and economic education is given, the role of the formation of engineering and economic specialists in the socio-economic development of the state is revealed, new aspects of the role of training this profile in the medium and long term are revealed.
Keywords: Великая Отечественная война; The Great Patriotic War; формирование конкурентоспособных специалистов; инженерно-экономическое образование; formation of competitive specialists; engineering and economic education